Late Prosthetic Shoulder Hemiarthroplasty after Failed Management of Complex Proximal Humeral Fractures - A. Panagopoulos; P. Tsoumpos; K. Evangelou; Christos Georgiou; I. Triantafillopoulos (Advances in Orthopedics)
Background. The purpose of this study was to report our experience with shoulder hemiarthroplasty in the context of old trauma. Methods. 33 patients with failed treatment for a complex proximal humeral fracture underwent prosthetic hemiarthroplasty. There were 15 men and 18 women with a mean age of 58.1 years. The average period from initial treatment was 14.9 months. Sequelae included 11 malunions, 4 nonunions, 15 cases with avascular necrosis (AVN) and 3 neglected posterior locked dislocations. Follow up investigation included radiological assessment and clinical evaluation using the Constant score and a visual analogue pain scale. Results. After a mean follow up of 82.5 months the median Constant score was 75.7 points, improved by 60% in comparison to preoperative values. Greater tuberosity displacement, large cuff tears and severe malunion were the factors most affected outcome. No cases of stem loosening or severe migration were noted. 60% of the patients were able to do activities up to shoulder level compared with 24% before reconstruction. Conclusions. Late shoulder hemiarthroplasty is technically difficult and the results are inferior to those reported for acute humeral head replacement, nonetheless remains a satisfactory reconstructive option when primary treatment fails.